The path to kina convertibility: An analysis of Papua New Guineaʼs foreign exchange market - Martin Davies; Marcel Schröder (Asia & the Pacific Policy Studies, 2022)
Abstract Papua New Guinea (PNG) has faced a foreign exchange (forex) shortage since 2015. The Bank of PNG has resorted to forex rationing to protect reserves, leading to a large backlog of orders and import compression. This paper surveys the structure of PNGʼs forex market and analyses recent market conditions. We argue that a real exchange rate depreciation is required to restore currency convertibility. We develop a forex market model that features a backlog of unmet orders which suggests that a frontloaded depreciation is preferred to an often‐favored gradual adjustment. Empirical results indicate that the governmentʼs large budget deficits have contributed to the forex shortage, highlighting the need for greater fiscal restraint. In the longer term, we argue for more exchange rate flexibility and forex allocation through competitive auction.